2023
DOI: 10.3389/fphar.2023.1192970
|View full text |Cite
|
Sign up to set email alerts
|

RIPK2: a promising target for cancer treatment

Abstract: As an essential mediator of inflammation and innate immunity, the receptor-interacting serine/threonine-protein kinase-2 (RIPK2) is responsible for transducing signaling downstream of the intracellular peptidoglycan sensors nucleotide oligomerization domain (NOD)-like receptors 1 and 2 (NOD1/2), which will further activate nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways, leading to the transcription activation of pro-inflammatory cytokines and productive inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Additionally, it plays a role in the advancement and metastasis of prostate cancer by maintaining c-Myc, a protein that promotes tumor development and invasiveness. Therefore, interventions targeting RIPK2 to degrade c-Myc, such as medicines or gene editing techniques, may hold promise in preventing prostate cancer [220,221] . Some research suggests that RIPK2 inhibitors have shown beneficial effects in both preclinical and clinical trials.…”
Section: Receptor-interacting Protein Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it plays a role in the advancement and metastasis of prostate cancer by maintaining c-Myc, a protein that promotes tumor development and invasiveness. Therefore, interventions targeting RIPK2 to degrade c-Myc, such as medicines or gene editing techniques, may hold promise in preventing prostate cancer [220,221] . Some research suggests that RIPK2 inhibitors have shown beneficial effects in both preclinical and clinical trials.…”
Section: Receptor-interacting Protein Kinasementioning
confidence: 99%
“…For instance, the small molecule inhibitor ALW-II-41-27 binds to the ATP-binding site of RIPK2, impeding its kinase activity. Studies conducted in vitro and in vivo have demonstrated its efficacy in inhibiting the proliferation and invasion of prostate cancer cells [220] . Another approach involves KB004, a humanized monoclonal antibody that induces internalization and degradation of RIPK2 by recognizing an epitope on its extracellular domain.…”
Section: Receptor-interacting Protein Kinasementioning
confidence: 99%
See 1 more Smart Citation